2003
DOI: 10.1097/00004424-200302000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Breast Lymphatic Pathways With an Indirect Computed Tomography Lymphography Using a Nonionic Monometric Contrast Medium Iopamidol

Abstract: Indirect CT-LG with iopamidol may have excellent potential for visualizing breast lymphatic drainage and for preoperative localization of breast sentinel lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 26 publications
5
84
2
Order By: Relevance
“…Such contrast agents may rapidly enter the venous capillaries, shunting lymphatic pathways after interstitial injection. This characteristic means that the optimal time window for CT imaging is very short [26]. Presently, the optimal CT window using water-soluble, non-particulate contrast agents has been known to be between 5 and 10 min after interstitial injection, which may considerably limit SLN navigation, particularly in gastrointestinal malignancies [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Such contrast agents may rapidly enter the venous capillaries, shunting lymphatic pathways after interstitial injection. This characteristic means that the optimal time window for CT imaging is very short [26]. Presently, the optimal CT window using water-soluble, non-particulate contrast agents has been known to be between 5 and 10 min after interstitial injection, which may considerably limit SLN navigation, particularly in gastrointestinal malignancies [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, under local anesthesia, 4 ml of undiluted iopamidol (Iopamiron 370; Nihon Schering, Osaka, Japan) was injected into the periareolar and peritumoral areas (2 ml at each site), followed by gentle massage for 60 s [5][6][7]. Contiguous CT images from the upper thorax to the axillary region were obtained before and immediately after administration of the contrast agent and massage.…”
Section: Dct-lgmentioning
confidence: 99%
“…We recently developed a new technique for detecting SLNs by interstitial multidetector-row computed tomography (CT)-lymphography using iopamidol, a widely available water-soluble non-ionic monometric contrast agent [5][6][7]. When we performed SLNB using both threedimensional CT lymphography (3DCT-LG) and the dye method, the SLN detection rate was 100% [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Suga et al (30) reported the results of a study of contrast-enhanced CT of the lymph nodes in a canine model and also reported the depiction of mammary lymph nodes in one human volunteer. In 1975, Weshler et al (31) described (a) "pneumomammography," in which oxygen was injected under pressure to inflate the breast, and (b) "pneumocystography," in which oxygen was used to inflate aspirated cysts.…”
Section: Galactographymentioning
confidence: 99%